Effects of emotion and reward motivation on neural correlates of episodic memory encoding: A PET study - Shigemune, Yayoi; Abe, Nobuhito; Suzuki, Maki; Ueno, Aya; Mori, Etsuro; Tashiro, Manabu; Itoh, Masatoshi; Fujii, Toshikatsu (Neuroscience research, 2010)
It is known that emotion and reward motivation promote long-term memory formation. It remains unclear, however, how and where emotion and reward are integrated during episodic memory encoding. In the present study, subjects were engaged in intentional encoding of photographs under four different conditions that were made by combining two factors (emotional valence, negative or neutral; and monetary reward value, high or low for subsequent successful recognition) during H 2 15O positron emission tomography (PET) scanning. As for recognition performance, we found significant main effects of emotional valence (negative > neutral) and reward value (high value > low value), without an interaction between the two factors. Imaging data showed that the left amygdala was activated during the encoding conditions of negative pictures relative to neutral pictures, and the left orbitofrontal cortex was activated during the encoding conditions of high reward pictures relative to low reward pictures. In addition, conjunction analysis of these two main effects detected right hippocampal activation. Although we could not find correlations between recognition performance and activity of these three regions, we speculate that the right hippocampus may integrate the effects of emotion (processed in the amygdala) and monetary reward (processed in the orbitofrontal cortex) on episodic memory encoding.